Factors Influencing Continuance Usage Intention Of E-Filing System Among Taxpayers In Malaysia - Thominathan, Santhanamery (2014)
In this current competitive environment, it is important for businesses to accentuate on continuance usage as the key for long term growth. It has been argued that the longer a business can keep a customer, the greater the revenue can be earned from that customer and the cost of serving the customer also declines. Malaysian Government has spent huge amount of money in developing the e-Filing system which is receiving much attention and there has been an upward trend in the adoption of the system among taxpayers in the first five years. However, while initial acceptance of information system (IS) is very important toward realizing IS success but its eventual success depend on its continued use rather than first-time use. In this vein, investigating the continuance usage intention of e-filing system is deemed to be important because as more citizens use the e-filing system the more operation and management cost can be reduced. As such, the purpose of this study was to examine the continuance usage intention of the e-filing system among taxpayers in Malaysia based on three important individual beliefs which is trust in the system, personality and optimism bias. The sample size comprises 731 taxpayers from the urban states of Peninsular Malaysia which comprises Penang, Perak, Selangor, Kuala Lumpur and Johor were collected and analyzed using Structural Equation Modeling (SEM).